Bar resilience to flybys in a cosmological framework. Issue 4 (19th July 2018) - Zana, Tommaso; Dotti, Massimo; Capelo, Pedro R; Mayer, Lucio; Haardt, Francesco; Shen, Sijing; Bonoli, Silvia
ABSTRACT: It has been proposed that close interactions with satellite galaxies can significantly perturb the morphology of the main galaxy. However, the dynamics of an already formed bar following the interaction with the external environment has not been studied in detail in a fully cosmological context. In this work, analysing the cosmological zoom-in simulation Eris2k, we study the effects that a very unequal-mass flyby crossing the stellar disc has on the stability of the pre-existing bar. We characterize the evolution of the bar strength and length showing that the perturbation exerted by the flyby shuffles the orbits of stars for less than one Gyr. After this time, the bar shows a remarkable resilience, reforming with properties comparable to those it had before the interaction. Our work shows that close unequal-mass encounters, the most frequent interactions occurring during the evolution of cosmic structures, have (i) an overall minor impact on the global evolution of the bar in the long term, still (ii) the effect is destructive, and (iii) a very weak interaction is sufficient to dismantle a strong bar leading to its "apparent death". As a consequence, due to the non-negligible duration of the bar-less period, a fraction of observed spiral galaxies classified as non-barred could be prone to bar formation.